Perlindungan Hukum dan Risiko Cacat Materiil Akta bagi Klien Tunanetra dalam Ketiadaan Pengaturan UUJN - Sari, Yenti Khofifah Nilam; Salsabillah, Silfiyana (JURNAL MINUTA, 2026)
Law Number 8 of 2016 on Persons with Disabilities explicitly recognizes persons with disabilities, including visually impaired persons, as legal subjects who are entitled to equal legal protection and legal certainty in all aspects of life, including civil legal relations embodied in authentic deeds. This reflects the principle of equality before the law. In notarial practice, notaries serve as public officials authorized to draw up authentic deeds under the Notary Office Act (UUJN). Article 16 paragraph (1) letter m of the UUJN mandates the reading of deeds before the appearers and witnesses to ensure that the parties fully understand and consent to the content of the deed. Legal issues arise when this obligation is applied to visually impaired appearers. Visual limitations prevent them from independently verifying the written deed against the oral reading conducted by the notary, resulting in complete reliance on the notary’s professionalism and good faith. The absence of specific technical regulations governing the reading and signing of deeds for visually impaired persons creates legal uncertainty and increases the risk of material defects in authentic deeds. This situation may affect the validity of deeds, expose notaries to civil and administrative liability, and weaken the protective function of deed witnesses. This research is a normative legal study employing statutory and conceptual approaches. The study concludes that the lack of explicit procedural standards undermines substantive legal protection and legal certainty, emphasizing the urgent need for inclusive and clear regulations to ensure accountable and nondiscriminatory notarial practices.